The impact of police contact on trust and police legitimacy in Belgium - Damme, Anjuli Van (Policing and society, 2017)
Personal contact with the police is mentioned as one of the key predictors of individuals’ opinions towards the police. But findings from earlier research contradict each other. Some researchers found an asymmetric relationship with a much stronger effect from unsatisfactory contact, compared with satisfactory contact, with regard to trust in the police and police legitimacy. Others found a more symmetrical relationship. In a way, these different findings can be due to different measures of trust and legitimacy. In the literature there is no consensus about the meaning and measurement of these concepts. The purpose of this study is therefore to test the (a)symmetrical relationship while taking into account criticisms about trust and legitimacy. More precisely, we consider trust in police procedural justice and trust in police effectiveness as two components of trust having an influence on police legitimacy in the form of moral alignment. Feeling an obligation to obey the police is considered as an outcome of moral alignment. We used path models in MPlus to do the analyses, which were conducted on data collected from the Social capital and Well-being In Neighbourhoods in Ghent (SWING) survey, Belgium. The results show a more symmetrical relationship between contact and both components of trust. Furthermore, trust in police procedural justice was found to be a stronger predictor for moral alignment than trust in police effectiveness. Moral alignment itself seemed to be a strong predictor for feeling an obligation to obey the police.